1994
DOI: 10.1143/jjap.33.6458
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Size Effects in Amorphous Diamond-like Carbon Superlattices

Abstract: Coordinare-free representations of the Riemann and Einstein tensors are obtained, and approximate diffeomorphism invariance is shown to exist for near-Rat simplicial geometries with sufficiently fat triangulations. Then, by finding the analogues of the contracted Bianchi identities for these near-Rat geometries, interdependence of the Regge equations is shown, and the relation to the coordinate degrees of freedom of the continuum is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…͑1͔͒; however, this requires knowledge of the effective mass for amorphous carbons. The effective mass found experimentally ͑using EELS͒ and theoretically 15,16 for amorphous carbons is m * = 0.87m e , while Silva et al 2,3 have shown a tunneling effective mass for amorphous carbon superlattices m * = 0.067m e . Assuming that the free-electron component in Eq.…”
Section: Figmentioning
confidence: 94%
See 1 more Smart Citation
“…͑1͔͒; however, this requires knowledge of the effective mass for amorphous carbons. The effective mass found experimentally ͑using EELS͒ and theoretically 15,16 for amorphous carbons is m * = 0.87m e , while Silva et al 2,3 have shown a tunneling effective mass for amorphous carbon superlattices m * = 0.067m e . Assuming that the free-electron component in Eq.…”
Section: Figmentioning
confidence: 94%
“…2,3 The nominal dimensions of the sample are contained in its name, where B140W80 signifies a barrier width of 140 Å and a well width of 80 Å, respectively. Cross-sectional samples for TEM were prepared by mechanical thinning and polishing, followed by ion beam polishing.…”
mentioning
confidence: 99%
“…It can even contribute to the tunneling current at room temperatures showing negative differential resistance ͑NDR͒ features. 12 Also, if we consider variations of the thickness of carbon films, then the thinnest part of the films can be considered for highest T t . Therefore, for b ϳ 1 V and d Ͻ 10 nm, up to 10 −6 of T t can be achieved.…”
Section: ͑1͒mentioning
confidence: 99%
“…8 Hence, direct tunneling signatures in carbon MIS structures at low bias or strong charge inversion at high bias has not been reported. 5,[9][10][11][12][13][14][15] In practice, the well-known negative differential conductance in oxide based MIS tunnel diodes or transistors has been suppressed due to the contribution of a large density of interface trap states 16,17 and limits high frequency operation. We have recently demonstrated negative differential resistance in a-C quantum well structures.…”
mentioning
confidence: 99%
“…14,15 Higher values of 1 -10 cm 2 V −1 s −1 have also been observed under special conditions of nanostructuring in the a-CN x films 16 and under superlattice conditions. 17 The small variation in the data as a function of substrate temperature is expected with the evolution of the bonding, especially the C-N sp 2 lone pair states and band gap. The variation is small, and we believe this could be due to the little variation observed in the unpaired defects measured by ESR.…”
mentioning
confidence: 90%